A STRUCTURAL AND KINETIC-STUDY OF CHLORINE CHEMISORPTION AND SURFACE CHLORIDE FORMATION ON CR(100) - Foord, J; Lambert, R (1982)
Chlorine adsorption on (1 × 1)-Cr(100) has been studied using AES, UPS, XPS, LEED, TDS and Δφ measurements. For gas exposures of <8.0 × 1018 molecules m-2. Cl2 adsorbs dissociatively with high sticking probability into an atomic overlayer. Continuous compression of an initial c(2 × 2) phase occurs as coverage increases, until a p(2 × 5) structure is formed with a ClCl nearest neighbour separation of 3.41 Å. In this coverage regime a single adsorbate induced band appears at -6.0 eV in UPS and the Cr(2p) and Cl(2p) binding energies remain constant in XPS. Thermal desorption occurs as CrCl, and the TD spectra exhibit a single peak which corresponds to an activation energy of 300-340 kJ mol-1. After higher gas exposures, chemical shifts in XPS and the appearance of additional bands in UPS reveal that epitaxial growth of chromium dichloride occurs. This halide phase has a twinned layer structure; it desorbs as CrCl2 with an activation energy of ∼240 kJ mol-1. The system now exhibits three-dimensional island growth, and the rate of corrosion of the chromium substrate is shown to be ∼0.02 that of overlayer formation. © 1982.